Crude Oil Price Shocks and Stock Returns: Evidence from Turkish Stock Market under Global Liquidity Conditions - Istemi Berk; Berna Aydogan (Institute of Energy Economics at the University of Cologne (EWI), 2012)
The purpose of this study is to investigate the impacts of crude oil price variations on the Turkish stock market returns. We have employed vector autoregression (VAR) model using daily observations of Brent crude oil prices and Istanbul Stock Exchange National Index (ISE-100) returns for the period between January 2, 1990 and November 1, 2011. We have also tested the relationship between oil prices and stock market returns under global liquidity conditions by incorporating a liquidity proxy variable, Chicago Board of Exchange's (CBOE) S&P 500 market volatility index (VIX), into the model. Variance decomposition test results suggest little empirical evidence that crude oil price shocks have been rationally evaluated in the Turkish stock market. Rather, it was global liquidity conditions that were found to account for the greatest amount of variation in stock market returns.
Keywords: C58; G15; Q43; Q47; 330; Oil Price Shocks; Stock Returns; Liquidity; VAR Model